SYNTHESIS AND CHARACTERIZATION OF SrAl2O4: Eu, Dy NANOMATERIALS - Victor Kadenge (American Journals Publishing, 2022)
One purpose of this study is to describe current advances made mostly in preparation of luminescence nanoparticles based on a study that has been published. In outlining the benefits and limitations of various synthesis methods, we highlight recent advances on SrAl2O4: Eu, Dy nanoparticles. Such durable substance has various advantages over its precursors, including being more stable, efficient, and much less poisonous. Its design of an efficient synthesis process for SrAl2O4 dopant particles. As a result, the average particle size ranges between 20 and 100 micrometers. For contemporary usage that require semi nanoparticles, the high particle diameter is constraining. Its resulting luminescence emission is heavily influenced by the morphology and shape, which may be adjusted by modifying the control parameters. As a result, substantial effort like the sol-gel technique, hydrothermal synthesis, laser synthesis, combustion fabrication, and solid country reaction, has acquired quite a few interest as a result of this. A lot of those methods, even though, are incompatible to enormous production and sustainable requirements. strong synthesis values, in general between 1300 and 1900 °C, with prolonged processing instances are required in the industrial processing of distinctly crystalline powders, especially for strong kingdom reactions has gone into developing new ways for obtaining nanoparticles while minimizing time-consuming, difficult, expensive, or inefficient preparation stages, as well as intrinsic toxicity or elemental shortage. Furthermore, the applicability of lasting luminous nanoparticles photovoltaic cells, biomedical scanning and identification, and safety encryption has piqued interest. Moreover, we discuss the production, characteristics, the uses of luminescent substances, as well as the problems and future of these substances.
Keywords: COVID-19, risk factor and Kabul city